Knowledge, attitudes, and practices regarding cardiovascular disease prevention among middle school students in China: a cross-sectional study - Xin Yang; Qiang Qin; Yifei Wang; Zhaopeng Ma; Qiurong Li; Fusheng Zhang; Yanbai Han; Hongli Wang (Frontiers Media S.A., 2024)
BackgroundThe prevalence of cardiovascular disease (CVD) is rapidly increasing globally. With a concerning increase among adolescents due to unhealthy habits, obesity, and hypertension, understanding the current status of knowledge, attitudes, and practices (KAP) related to CVD prevention among middle school students is crucial for developing effective school-based health programs to prevent CVD.MethodsThe analytic cross-sectional survey is used in questionnaires to assess KAP related to CVD prevention among middle school students (N = 17,731) from 50 schools across 16 provinces in China in June-July 2023. The pass rate of KAP scores is categorized as good and poor. Independent predictors of good KAP of CVD prevention are ascertained using a binary logistic regression model.ResultsThe study surveyed 8,118 (45.78%) junior high school students and 9,613 (54.22%) high school students. The overall mean [standard deviation (SD)] for the knowledge, attitude, and practice scores were 26.88 (8.12), 53.53 (7.22), and 39.80 (5.96), respectively. The knowledge scores had the lowest pass rate at 56.89%. Only 6.83% of the students know "the definition of blood pressure in adolescents." Attitudes toward health were positive, though the attitude regarding "the danger of prolonged sedentary to cardiovascular health" scored lowest at 73.55%. The practice section had a pass rate of 89.30%; 40.27% of students reported that they spend more than an hour a day on screens. Only one-third of the students would go to bed before 12 o'clock. In univariate analysis, junior high school and high school students differed significantly in knowledge and practice (p < 0.001), but attitude did not differ significantly (p = 0.103).ConclusionThe majority of students lack sufficient knowledge about CVD. It is also found that socioeconomic background, family environment, and educational levels have an impact on cardiovascular health behaviors among students. Strengthening health education involving students, parents, teachers, and communities is essential to promote health knowledge and practices among adolescents.